Depression, physical function, and disease activity associated with frailty in patients with rheumatoid arthritis. Issue 5 (3rd September 2021) - Kojima, Masayo; Kojima, Toshihisa; Waguri-Nagaya, Yuko; Takahashi, Nobunori; Asai, Shuji; Sobue, Yasumori; Nishiume, Tsuyoshi; Suzuki, Mochihito; Mitsui, Hiroto; Kawaguchi, Yohei; Kuroyanagi, Gen; Yasuoka, Mikako; et al.
Abstract: Objectives: To investigate the clinical and psychosocial backgrounds of frailty in rheumatoid arthritis (RA) patients. Methods: Patients with RA between 40 and 79 years of age who visited university hospitals in an urban area were recruited. Well-validated self-reported questionnaires were used to evaluate patient physical function (Health Assessment Questionnaire, HAQ), depressive symptoms (Beck Depression Inventory-II, BDI-II), and frailty (Kihon Checklist). A 28-point Disease Activity Score (DAS-28) was calculated to evaluate RA disease activity. Results: A total of 375 RA patients, 323 of whom were women, were enrolled (average age: 65.2 ± 9.7 years; average disease duration: 16.6 ± 11.9 years). The prevalence rates of frailty, working-age (40–64 years), young-old (65–74 years), and old-old (≥75 years) patients were 18.5, 28.8, and 36.6%, respectively. Higher age and longer disease duration were associated with frailty. Multivariable logistic regression analysis revealed that HAQ, DAS-28, and BDI-II scores were independently associated with frailty in RA patients. Conclusion: Frailty is common, even among working-age RA patients. Physical function, disease activity, and depressive symptoms were independently associated with frailty. A multidisciplinary intervention approach, along with adequate pharmacological therapy, may promote successful aging in patients with RA.